‫إدارة ‬‫اﻟﺘﺪﻓﻘﺎت‬ ‫اﻟﻨﻘﺪﻳﺔ‬ ‫ﻓﻲ‬ ‫ﻇﻞ‬ ‫أﻧﻈﻤﺔ‬ ‫اﻟﺪﻓﻊ‬ ‫اﻟﺘﻘﻠﻴﺪﻳﺔ‬ ‫و‬ ‫اﻹﻟﻜﺘﺮوﻧﻴﺔ‬ ‫دراﺳﺔ‬ ‫ﻣﻴﺪاﻧﻴﺔ‬ ‫ﺑﻤﺆﺳﺴﺘﻲ‬‫ﺑﺮﻳﺪ‬ ‫اﻟﺠﺰاﺋﺮ‬ ‫و‬ ‫ﺗﻮزﻳﻊ‬ ‫اﻟﻜﻬﺮﺑﺎء‬ ‫و‬ ‫اﻟﻐﺎز‬ ‫ﻟﻠﺸﺮق‬ ‫ ‫ﺳﻮق‬ ‫اﻫﺮاس‬ ‫‪‬‬ - ‫ﻣﺤﻤ ﺪ‬‫اﻟﻴﻤﻴﻦ‬ ‫ﺑﻦ‬ ‫ﺛﻠﺠﻮن‬; ‫ﻣﺤﻤﺪ‬‫ﻓﺮﻳﺪ‬ ‫ﺑﻦ‬ ‫ﺑﺎرش‬ (My University, 2017)
In the light of recent technological developments, the Object of a real position of the updated payment methods has become necessary or even an obsession with the evolution of Algerian Companies which aspires to a market economy and institution competing to the Foreign countries in the light of the large neighborhoods realized by the institutions of the developed countries in this field, and we have tried through this study, which lasted nearly four months to deal with the subject of cash flow management in traditional and electronic payment systems, the purpose of which is to demonstrate how these tools can contribute to the efficiency of these institution in the management of cash flow management, and to this end we have allocated our research to two main axes: the theoretical part, where we have approached the different basic concepts on the subject, the descriptive approach in addition to the historical method in certain stages of the study, in the practical part ,we opted for a case study , concluding with a series of results, the most important being the absence of the Culture of electronic payment at Algerian dealers ,which prompts us to propose to you to encourage the management of the electronic means of payment and the consolidation of this culture among the members of the society by the implementation of the material and human means necessary this which would be beneficial for these companies , especially in the lifting of financial income and the efficiency of cash flow management.